Endodontic applications of cone beam computed tomography: case series and literature review - Francesc Abella; Kala Morales; Iván Garrido; Javier Pascual; Fernando Duran-Sindreu; Miguel Roig (Ariesdue, 2015)
Cone beam computed tomography (CBCT) is a relatively new method that produces three-dimensional (3D) information of the maxillofacial skeleton, including the teeth and their surrounding tissue, with a lower effective radiation dose than traditional CT scans. Specific endodontic applications for CBCT are being identified as the use of this technology becomes more common. CBCT has great potential to become a valuable tool for diagnosing and managing endodontic problems, as well as for assessing root fractures, apical periodontitis, resorptions, perforations, root canal anatomy and the nature of the alveolar bone topography around teeth. This article aims to review cone beam technology and its advantages over CT scans and conventional radiography, to illustrate current and future clinical applications in endodontic practice, and to highlight areas of further research of CBCT in endodontics. Specific case examples illustrate how treatment planning has changed with the images obtained with CBCT technology compared with only periapical radiography.